Improving Students' Collaboration Skills by Using STEM-Engineering Design Process (EDP) on Motion and Force Materials - Fatiin, Jihan Mutiara; Winarno, Nanang; Samsudin, Achmad; Wahyuningsih, Yuyun; Nurhaida, Popi (PILLAR OF PHYSICS EDUCATION, 2024)
Along with the times, globalization has an increasingly obvious impact with opportunities and challenges that every individual must face simultaneously without exception. Education has an important role in shaping the nation's generation, which is ready to face the challenges of the 21st century. Indonesia has made efforts in this regard through the implementation of the Merdeka Curriculum which prioritizes the 6 pillars of the Pancasila Student Profile which is considered the basis for shaping the character of students. Collaboration skills are part of the pillar of mutual cooperation in the Pancasila Learner Profile and are very important for students to develop. This study aims to analyze the improvement of students' collaboration skills by using the STEM-Engineering Design Process (EDP) on motion and force. This research used a pre-experimental method with One Group Pretest-Posttest. The data collection tool used in this study is a Self-Assessed Contribution Skills (SACS) questionnaire. This research was conducted in one of the schools in Bandung, Indonesia. The subjects in this study were 34 seventh-grade students consisting of 16 boys and 18 girls. The results showed a significant increase in students' collaboration skills with a mean pretest of 63% and a mean post-test of 67%. The N-Gain score on the Information Sharing dimension was 0.24, the Group support dimension was 0.07, and the Group Learning dimension was 0.08. Based on the study's results, STEM-Engineering Design Process (EDP) learning can be an alternative for teachers in improving students' collaboration skills, especially in science lessons. Keywords :STEM, Engineering Design Process, Collaboration Skills.